ANALISIS CITRA MEREK, HARGA, PELAYANAN, DAN PROMOSI TERHADAP KEPUASAN KONSUMEN DI KOTA PALEMBANG (STUDI KASUS KONSUMEN GRAB) - Kurniawan, Muhammad; Hildayanti, Siti Komariah (Jurnal Ecoment Global, 2019)
This research is entitled Analysis of Brand Image, Price, Service, and Promotion of Consumer Satisfaction in Palembang City (Consumer Case Study of Grab) Palembang. The purpose of this study is to find out the effect of Brand Image, Price, Service, and Promotion together and partially on Consumer Satisfaction as well as to determine the effect of variables that have the most significant effect on Grab Palembang Customer Satisfaction. This research method uses the multiple regresssion model method which is a research design that will reveal the collective influence of the independent variable on one dependent variable. The data used are primary data and secondary data collected through questionnaires and data from Grab consumers directly. The total population is 3262 respondents and the sample is 256 respondents from consumers who use services from Grab. The results of the study show that the Consumer Decision partially has three influential variables, namely Price, Service, and Temporary Promotion Brand Image is not too influential on Consumer Satisfaction. Meanwhile, simultaneously the four variables have a significant influence on customer satisfaction Grab Palembang. This is evidenced by regression analysis on variables Brand Image, Price, Service, and Promotion.Keywords: Marketing Mix, Brand Image, Price, Service, Promotion, Consumer Satisfaction.